Gene- Environment Interaction in Speech and Language Development- A Case Study of Monozygotic Twins - Maya Sanghi; Sidheshwar Pandey; Hetal Shah (Journal of All India Institute of Speech and Hearing, 1970)
Heritability of speech and language disorders is not a simple, straightforward process. There is good evidence that genetic factors play a role in the etiology of speech and language impairment; twin data may help us arrive at a clearer conception of the phenotype as well as quantifying the extent of the genetic contribution. By investigating identical and non-identical twins, researchers have been able to deduce that genetic variability plays a big role in determining whether or not a child will have developmental language problems. The current scientific view is that neither genetics nor environment is solely responsible for producing individual variation, and that virtually all traits show gene-environment interaction. In identical twins, DNA is same and they are brought up in the same surroundings hence case studies of the identical twins help us to study the effect of genetics, environment or both. Case studies also help in better understanding about the nature of the disorder. Aims of the study were 1)To improve our understanding of the nature of the speech and language disorder in identical twins and thereby facilitate further research in this area.2)To share the experience of working with a pair of identical twins with concomitant speech and language disorders. For assessment, 3D Language Acquisition test, Linguistic Profile Test, Stuttering Severity Index, Stuttering Chronicity Prediction Checklist and Pure Tone Audiometry were done. Possible causes of stuttering in the twins under study may be the interaction of genetic predisposition and precipitating factors such as home environment, competitive pressure etc. This paper also highlights the need for the clinicians to be alert about the speech language problems twins are prone to and the need to work in close co-operation with the pediatricians to prevent the developmental communication disorders in this population.